PENGARUH PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN PT. UNILEVER INDONESIA Tbk. TAHUN 2005 – 2012 - Yuliani, Rina; Salim, Ubud (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this study was to examine the effect of the level of accounts receivable turnover on profitability as measured by Return On Assets. Object of study, namely PT. Unilever Indonesia Tbk year period from 2005 to 2012. This study uses quantitative descriptive and explanatory nature replica consisting of two variables are receivable turnover as the independent variable and ROA as the dependent variable. The type of data used is quantitative data and data sources used are secondary data. Data collection techniques are technical documentation. Method of data analysis used in this study is a simple regression analysis and tested by t-test. The test results showed that the level of accounts receivable turnover has a significant effect on profitability. These results can be seen in the R Square of 0.795, which means the relationship between the profitability of the accounts receivable turnover has a very strong relationship. Results of this study confirmed the hypothesis testing results through the t-test showed a significance 0.018 receivable turnover is below 0.05, which means the accounts receivable turnover rate have a significant effect on profitability (ROA). Keywords: Accounts Receivable, Accounts Receivable Turnover Rate, Profitability (Return On Assets).